PENGELOLAAN FASILITAS PADA OBJEK WISATA PANTAI PRAPAT TUNGGAL KABUPATEN BENGKALIS - Arliani Faulina; Andi Moh Rifiyan Arief (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Management is a process that consists of planning, organizing, implementing and monitoring, in which each field uses science and art on a regular basis in order to be able to achieve certain predetermined goals. This research was conducted by the author in Prapat Tunggal Beach, Bengkalis Regency. This research was conducted by the author with the aim of knowing the general description of the management of facilities at the Prapat Tunggal Beach Tourism Object and to determine the management of the facilities at the Prapat Tunggal Beach Tourism Object, Bengkalis Regency. The author uses qualitative methods in this study to get a picture of what happened in the Prapat Tunggal Beach Tourism Object, Bengkalis Regency. Researchers explain the actual conditions and conditions based on data and information in the field. Data collection techniques that researchers use in this study are observation, interviews and documentation. Based on the research that has been done on the Prapat Tunggal Beach Tourism Object, the management of the facilities at the Prapat Tunggal Beach Tourism Object until now has not been going well because many facilities are still poorly maintained.Keywords: Management, Facility and Prapat Tunggal Beach.